2010
DOI: 10.1016/j.postcomstud.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Europeanization of social movements in the Czech Republic: The EU and local women’s groups

Abstract: The goal of this paper is to analyse the impact the EU has had on Czech women’s groups since the1990s. Drawing on both Europeanization and social movement theories, the first section defines the theoretical framework of the paper. The second section is focused on the impact of changes in the funding of women’s groups which, since the end of the1990s, have relied more than before on European funding. The third section analyses the shift in the political context and the domestic political opportunity structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 7 publications
0
18
0
4
Order By: Relevance
“…The precarity faced by GS teachers is thus manifold: it concerns the relatively low wages, 7 blurry assessment of their pedagogical input, and the uncertain status of their programmes. The situation is further exacerbated by the fact that gender equality and its benefi ts for society are still far from established within the public discourse, as research into social movements has shown (Císař, Vráblíková 2010;Císař 2008). This reluctance to acknowledge the merits of GS on almost all levels of society has been associated with geopolitically perceived historical developments and their interpretation, which frames emancipation as a matter of the past and feminism as an alien import (Hašková, Uhde 2009;Havelková, OatesIndruchová 2014).…”
mentioning
confidence: 99%
“…The precarity faced by GS teachers is thus manifold: it concerns the relatively low wages, 7 blurry assessment of their pedagogical input, and the uncertain status of their programmes. The situation is further exacerbated by the fact that gender equality and its benefi ts for society are still far from established within the public discourse, as research into social movements has shown (Císař, Vráblíková 2010;Císař 2008). This reluctance to acknowledge the merits of GS on almost all levels of society has been associated with geopolitically perceived historical developments and their interpretation, which frames emancipation as a matter of the past and feminism as an alien import (Hašková, Uhde 2009;Havelková, OatesIndruchová 2014).…”
mentioning
confidence: 99%
“…When studying impacts attributed to Europe, scholars have usually chosen the top-down Europeanization approach either to study what happens at the European level and the implications for the feminist CSOs participating in an EU umbrella organisation (Hoskyns 1996;Jacquot 2001;Ramot 2006), or to study what happens at the national level when Europe hits home, giving more or less power to CSOs according to the political opportunity context for gender equality in the EU (Cullen 2014) or changing the inter-organisational relations between women's CSOs in the country (Císař and Vráblíková 2010;Karlberg and Jacobsson 2015). Indeed, the few studies analysing the EWL focus on the supranational level, i.e., the EWL lobbying strategies, its professionalisation and its Brussels secretariat (Cavaillé 2005;Helfferich and Kolb 2001;Pauget 2009;Strid 2009) or on the EWL organisational impacts on its Swedish coordination (Karlberg 2013).…”
Section: An Interactional and Sociological Perspective On Europeanizamentioning
confidence: 99%
“…Prekérnost vyučujících genderových studií je tedy různorodá: týká se relativně nízkých mezd, 9 nejasného hodnocení jejich pedagogického výkonu i nejisté pozice samotných programů. Celou situaci dále zhoršuje skutečnost, že genderová rovnost a její společenský přínos nejsou ani zdaleka pevnou součástí veřejné-ho diskursu, jak ukázal výzkum sociálních hnutí (Císař, Vráblíková 2010;Císař 2008). Neochota uznat přínos genderových studií na téměř všech společenských úrovních bývá spojována s geopoliticky vnímanými dějinnými procesy a jejich interpretací, která pojímá emancipaci jako věc minulosti a feminismus jako cizí import (Hašková, Uhde 2009;Havelková, Oates-Indruchová 2014).…”
Section: Feministická Pedagogika Se Protíná S Neoliberální Univerzitounclassified